Educational role of the nurse in relation to sexual behavior of junior high school students - Brodowicz-Król, Magdalena (Journal of Education, Health and Sport, 2019)
Human sexuality and sexuality in modern times are widely discussed topics. There are many publications that deal with this issue. This is perhaps due to the following global. socio-cultural changes, the return of which is unknown in the long run. The transformations concern the perception of a sense of gender identity. Scholars wanting to capture this extremely rich reality in a certain framework using a variety of tools. They do this rarely bypassing contexts, in line with prevailing trends, which prevents them from looking objectively at the subject of their research. Such research germinates with information chaos that floods us all pages. Aim : The purpose of the work is the educational role of the nurse in youth attitudes towards sexual behavior. Material and Methods : The research was carried out at the turn of April and June 2014. The study involved 94 students from two schools from the Junior High School in Wólka Pełkińska, Podkarpackie Province and from G Junior High School No. 9 in Lublin, Lubelskie Province. The diagnostic method that was used in the study was the diagnostic survey. The research tool used was the scale "Attitudes of junior high school students towards sexual behavior". It consists of 21 questions, of which eight are questions from the record. The database was created and statistical analyzes were carried out based on Statistica 9.1 computer software ( StatSoft , Poland). Rezults : The relationships that were shown in the description of the research of this work could result in pedagogical practice. Knowing what relationships prevail in the chosen topic, one could take specific pedagogical actions. Such activities would be, for example, the orientation of school curricula of knowledge subjects to family life, and more specifically topics in the field of premarital chastity as well as sex education. However, this process could not be left without control or specifically planned actions. Conclusion : Selected research tools have proved to meet the needs of the research problem posed. Thanks to the interpretation of the results obtained thanks to them, it turned out that there was a relationship that was sought in the research. It says that the attitudes of junior high school students towards sexual behavior are directly related to social conditions. The hypotheses put forward at work proved successful - the gender structure differentiates attitudes of junior high school students towards sexual behavior.